MEANING-EXPLICATIONS OF VERB âSEEINGâ IN LIO LANGUAGE - I. D. Koroh, Lanny (Lingual: Journal of Language and Culture, 2015)
This study proposes a new perspective in analyzing the state verb seeing in Lio language, Flores. The verbal data was collected by field-observation, and interview. The collected data was analyzed through the application of Natural Semantic Metalanguage theory (NSM) designed to explicate all meanings. It turns out that the state verb: Kile âseeâ has various types of lexicon explaining the different meanings in various forms